PF.71 We Have Diagnosed Ventriculomegaly – What Happens Next?. (26th April 2013) - Lacey, L; Satodia, P; Mehta, H; Mukherjee, S
Abstract : Ventriculomegaly is defined as dilatation ≥10 mm of the fetal cerebral lateral ventricles on ultrasound at 20 weeks gestation 1 2 . Aim: To assess the aetiology and neurological outcomes of ventriculomegaly at a University hospital from 2009–2012. Methods: 35 women with ventriculomegaly were identified on anomaly/fetal medicine scans between 20 to 30 weeks of gestation. They were investigated for aneuploidy, infections and further abnormalities. Long term neurological outcomes including the differences between mild (10–12 mm), moderate (13–15 mm) and severe(≥16 mm) ventriculomegaly in unilateral/bilateral and stable/progressive cases were examined. Results: Ultrasound scanning data: 26 women were offered invasive testing for aneuploidy, it was contraindicated or not appropriate in 9 patients. 5 women accepted invasive testing, 12 declined and 9 are still considering. Karyotyping was normal in all 5 women. 31 women had a negative TORCH screen. 13 women had a fetal MRI scan. Apgar scores were normal in all babies. 7 out of 18 babies with stable or progressive ventriculomegaly had abnormal cranial USS or MRI postnatally. All babies with mild ventriculomegaly at diagnosis have no developmental abnormalities currently. 2/7 babies with moderate ventriculomegaly and 1/2 babies with severe ventriculomegaly have delayed development. Conclusion: Ventriculomegaly of >13 mm can indicate a change of prognostic outcome. References: Melchiorre. K, Bhide. A, Gika. A.D, Pilu. G & Papageorghiou A.T. Counselling in isolated mild fetal ventriculomegaly. Ultrasound Obstet Gynaecol 2009;34:212–224. Sethna. F, Tennant. P.W.G, Rankin. J & Robson. S.C. Prevalence, Natural History and Clinical Outcome of Mild to Moderate Ventriculomegaly. Obstetrics & Gynaecology 2011;117:867–876.